ANALISIS HUKUM TENTANG HAK CIPTA SEBAGAI JAMINAN FIDUSIA UNTUK MENDUKUNG PERKEMBANGAN EKONOMI NASIONAL - Hermanto (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
This study aims to legally analyze the fiduciary guarantee that uses copyright as the object of the guarantee, as well as its relevance to the national economy. This study uses a normative juridical analysis and a statute approach, while the legal materials in this study consist of three types, namely primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of research and analysis of legal sources, it can be concluded that Copyright is exclusive and has economic value that fulfills the object of its rights, therefore it can become the object of a fiduciary guarantor that can be transferred but must first be registered in order to obtain protection for the guarantee holder in the form of a fiduciary deed. who have special privileges.